Measuring the effects of COVID-19 on mental, physical, and economic conditions of Saudi residents - Agarwal, Jyoti; Zeeshan, Zeeshan; Syed, Mohammad Haider; Asif, Mohammad (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of the COVID-19 pandemic on individuals’ well-being, focusing on the interplay between income reduction, mental health, preventive measures, and overall happiness. Using an online survey of 215 respondents, the study employs principal component analysis (PCA), structural equation modeling (SEM), and descriptive statistics to analyze key relationships between income loss, mental health, COVID-19 precautions, and happiness. The results reveal a significant negative correlation between income loss and happiness, indicating that financial insecurity during the pandemic adversely affected well-being. Mental health also played a critical role in shaping happiness, while adherence to COVID-19 precautions had a positive influence on well-being. However, the direct link between income loss and mental health was found to be insignificant. The study underscores the complex interdependencies between financial stability, mental health, and precautionary behaviors in determining individual well-being during a global health crisis. Policymakers should prioritize mental health interventions, income support programs, and public health measures to mitigate the pandemic’s adverse effects. Expanding access to counseling services, strengthening social support systems, and reinforcing adherence to COVID-19 precautions will be essential in enhancing public well-being. The findings provide a foundation for future research on crisis-driven well-being determinants.